2018
DOI: 10.1016/j.ijcard.2018.06.061
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin reduces TGF-β1-induced SMAD2/3-dependent human ventricular fibroblasts differentiation: Role of protein phosphatase activation

Abstract: This proof-of-concept study using an in vitro experimental cell culture model identifies the protective role of simvastatin against TGF-β1-induced hVF transformation into activated myofibroblasts through activation of protein phosphatase, a novel target that can be therapeutically modulated to curb excessive cardiac fibrosis associated with maladaptive cardiac remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 46 publications
2
15
1
Order By: Relevance
“…Myofibroblasts are defined by excessive α-SMA expression and EcM protein secretion (5,25). The present study demonstrated that TGF-β1 significantly promoted fibroblast differentiation and ECM protein expression, which is in accordance with the findings reported by previous studies (30,31,35). However, pre-incubation with ATV inhibited the TGF-β1-stimulated fibrotic response in hVFs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Myofibroblasts are defined by excessive α-SMA expression and EcM protein secretion (5,25). The present study demonstrated that TGF-β1 significantly promoted fibroblast differentiation and ECM protein expression, which is in accordance with the findings reported by previous studies (30,31,35). However, pre-incubation with ATV inhibited the TGF-β1-stimulated fibrotic response in hVFs.…”
Section: Discussionsupporting
confidence: 92%
“…Abnormal proliferation of CFs is the major cellular pathological basis of cardiac fibrosis. Increasing evidence suggests that TGF-β1, a key pro-fibrotic cytokine, can promote cF proliferation (30,31), which was confirmed in the present study. Furthermore, TGF-β1 has been demonstrated to be markedly and consistently activated in various cardiovascular diseases, including myocardial hypertrophy and myocardial infarction (32,33).…”
Section: Discussionsupporting
confidence: 88%
“…HCF activation and differentiation into myofibroblasts promote cardiac fibrosis progression; however, the underlying mechanisms of CM-fibroblast communication in cardiac fibrosis and myofibroblast phenotypic expression that are regulated by exosomes remain unclear. Several studies demonstrated that SIM had an anti-fibrosis effect, such as reducing TGF-β1-induced SMAD2/3-dependent pathway activation and promoted human ventricular fibroblasts differentiation [45]. It also alleviated cardiac fibrosis-induced infarction by up-regulating TGF-β receptor III expression [25].…”
Section: Discussionmentioning
confidence: 99%
“…Rosuvastatin, being hydrophilic, requires active transportation via organic anion transporting polypeptide 1B1 while lipophilic statins can passively diffuse into the cells . Although several prior in vitro studies have demonstrated statin‐induced prevention of differentiation to myofibroblasts, their ability to de‐differentiate already‐differentiated myofibroblasts is hitherto largely unknown. In addition to α‐SMA, the reduced expression of the negative regulator of fibrosis, Sprouty1, was reversed by simvastatin (Supporting Information, Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Statins are inhibitors of 3‐hydroxy‐3‐methyl‐glutaryl‐coenzyme A (HMG‐CoA) reductase commonly prescribed for their lipid‐lowering effects in patients at risk of HF. Several prior in vitro studies have demonstrated statin‐induced prevention of differentiation to myofibroblasts, but their ability to de‐differentiate already‐differentiated myofibroblasts is unclear. Further, the impact of statins on human ventricular fibroblasts (hVFs) in HF patients is also not known.…”
Section: Introductionmentioning
confidence: 99%